Climate-related variations in atmospheric Sb and Tl in the EPICA Dome C ice (East Antarctica) during the past 800,000 years - BARBANTE, Carlo; Boutron; Cf; Hong (Global Biogeochemical Cycles, 2013)
A record of antimony (Sb) and thallium (Tl) from the European Project for Ice Coring in Antarctica (EPICA) Dome C Antarctic ice core provides the characteristics of climate-related natural changes in concentrations and fluxes of these toxic elements over the time period back to Marine Isotope Stage 20.2, similar to 800kyrB.P. A strong variability in concentrations and fluxes are observed for both elements, with considerably higher values during glacial maxima and lower values during intermediate and warm periods. Rock and soil dust accounts for, on average, 58% of Sb and 76% of Tl in ice during glacial maxima. This contribution remains significant during warm periods, accounting for 21% for Sb and 27% for Tl. The contribution from volcanoes appears to be very important particularly for Tl when climatic conditions become warmer, with an estimated volcanic contribution of 72% for Tl during interglacials. The sea-salt contribution is significant for Sb, particularly during intermediate climatic periods, with an average contribution of 17%. This sea-salt contribution is most likely caused by greater production of sea salt from highly saline frost flowers and relatively more efficient transport of Sb-enriched sea-ice salt from source areas on the East Antarctic Plateau. Our ice core data, along with snow data recently reported from the Antarctic snow layers at Dome Fuji, shows that the present-day Sb flux (6.6ng/m(2)/yr) is approximately double the highest natural level (2.8ng/m(2)/yr) during glacial maxima throughout the last successive eight glacial/interglacial cycles. This result indicates that human activity has induced the greatest perturbation of the atmospheric cycle of Sb ever experienced over a period of similar to 800 kyr in the most remote area on Earth.